Twin nucleation and variant selection in Mg alloys: An integrated crystal plasticity modelling and experimental approach. (December 2020) - Paramatmuni, Chaitanya; Zheng, Zebang; Rainforth, W. Mark; Dunne, Fionn P.E.
Abstract: Extension twin nucleation and variant selection in magnesium alloy WE43 is investigated in experimentally characterised and deformed microstructures replicated in crystal plasticity models. Total stored (dislocation) energy density is found to identify the experimentally observed locations of twins which are not otherwise explained by global Schmid factors or local resolved shear stress criteria. A critical total stored energy of the order 0.015 Jm -2 is determined below which twin nucleation does not occur. The total stored energy density explains the locations of the observed twins and the absence of twins in parent grains anticipated to be favourable for twin nucleation. Twin variant selection has been shown to be driven by minimising locally stored shear energy density, while the geometric compatibility and strain compatibility factors only aid in partial prediction. All experimentally observed variants were correctly determined. Highlights: The extension twins nucleate within unfavourable parent grain orientations. These twins have low/negative global Schmid factors and the parent grains show negative local resolved shear stresses. The stored energy density identifies the twin nucleation sites. A new shear stored energy density criterion explains the twin variant selection.